Is Bronchiectasis (BE) Properly Investigated in Patients with Severe Asthma? A Real-Life Report from Eight Italian Centers - Giovanna Elisiana Carpagnano; Vitaliano Nicola Quaranta; Claudia Crimi; Pierachille Santus; Francesco Menzella; Corrado Pelaia; Giulia Scioscia; Cristiano Caruso; Elena Bargagli; Nicola Scichilone; Eva Polverino (Journal of Respiration, 2023)
Introduction: Asthma and bronchiectasis are often partners in a complex but uneven relationship with asthma receiving more attention. The aim of this study is to describe how bronchiectasis is investigated in some Severe Asthma (SA) Centers, scattered throughout the Italian territory. Materials and Methods: We enrolled 92 patients with SA and bronchiectasis from eight Italian SA Centers and recorded diagnostic approaches to investigate SA and bronchiectasis at the time of enrollment (T0), at the 6-month (T1), and at the 12-month (T2) follow-up visits. Results: A statistically significant heterogeneous diagnostic approach emerged across the centers under study. In fact, while, as expected, all involved centers made an in-depth investigation of SA, only a few of them provided a complete investigation of bronchiectasis in order to provide specific treatment. Discussion: This real-life multicenter study confirmed that patients with coexistent SA and bronchiectasis are mainly investigated for pheno-endotyping asthma but rarely for the complete assessment of bronchiectasis. We believe that the diagnostic flowchart of SA patients with suspicion or confirmed bronchiectasis needs to be clarified and implemented as the association of these conditions strongly influences the final outcome and management of these patients.